Interpersonal and Intrapersonal Intelligence as Predictors of Bullying Behavior Tendency among Junior High School Students in Indonesia - Yuli Asmi Rozali; Seraya Herman; Ricky Owen; Novendawati W. Sitasari; Marhisar Simatupang (Jurnal Ragam Pengabdian, 2026)
Bullying is a significant problem that requires special attention from educators, parents, and the government, as it can have a profound impact on the victims. Victims of bullying often experience feelings of pressure and frustration, which can lead to depression and even suicidal attempts. The inability of students to interact with their peers in the school environment is suspected to contribute to the emergence of bullying behavior. This study aims to analyze the influence of interpersonal and intrapersonal intelligence on bullying behavior tendencies among junior high school students in Indonesia. A quantitative-causal comparative research design was employed, with a sample of 400 students selected using cluster sampling. The research instrument was validated using construct validity (r ≥ 0.3) and reliability (alpha Cronbach ≥ 0.7). The results showed a significant negative relationship between interpersonal intelligence (β = -0.155) and intrapersonal intelligence (β = -0.841) with bullying behavior tendencies (p < 0.05). The findings suggest that both interpersonal and intrapersonal intelligence are significant predictors of bullying behavior tendencies among junior high school students in Indonesia.